The Present and Future Vitality of the Kejaman Language in Sarawak - Amee, Joan (Centre for Language Studies, 2015)
The Kejaman language is one of 46 languages found in Sarawak. Kejaman is a very small, aristocrate sub-group of the Melanau. With only 500 speakers, the Kejaman language is believed to be in danger of being lost from the linguistic landscape in Sarawak. The study describes the language use of the Kejaman people in order to determine the vitality of the language. The specific aspects studied are the language use of the Kejaman people across age groups, the domains in which Kejaman language is strong and domains where other languages are coming in. Questionnaires were administered to 40 Kejamans residing at Kampung Kejaman Neh Long Liten. The results of this study showed some interesting findings. Firstly, according to the EGIDS level (Ethnologue: Languages of the World, 2013), Kejaman language is “In trouble: EGIDS 6b” but the results of the survey had proven otherwise-it is at EGIDS 6a (vigorous). Secondly, different from the common scenario of other indigenous languages, the older generations are not the only active users of the language. Finally, all the respondents (100%) mentioned that they are proud to use Kejaman language. Ironically, the only domain in which Kejaman language is still strong is the family and other domains are taken over by Bahasa Melayu and other languages.